Aplikasi Pembelajaran Matematika di SMP Negeri 2 Mojolaban Berbasis Android - Susanto, Edy; Puspitasari, Norma; Fitri, Liza Aulia (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Mathematics is a subject that is often considered difficult by most students do not like math lessons. In this pandemic period learning methods use online systems so that teachers are not obliged to face-to-face with students. This makes students overwhelmed with this one subject. The students only get an explanation of learning through google meet / zoom. Sometimes signals and less supportive data packets become a barrier to listening to learning so that some of them are difficult to accept explanations from teachers. Based on the author's observations, the solution to the problem is to develop a system that includes a mathematics curriculum, not a curriculum but also practical problems and mathematics video tutorials. To allow students to play the video again if they don't understand the topic of mathematics. The author's method of developing this mathematics learning application uses the Multimedia Development Life Cycle (MDLC) method. Applications created using coded programming blocks. The final result obtained by making this mathematics learning application students or users can learn online not limited to time and place. With system results that can be accessed by admins and users. For admin access rights, namely student data, class data, test periods, question banks, practice questions, test questions, assignment data, assignment report data, student data report, per- Chapter grade data report, and per-student grade report. As for users, they can access learning materials, question exercises, question banks, learning videos, practice questions, tests, and assignments. The disadvantage of this Mathematics Learning Application is that there is no live chat menu feature with mathematics subject teachers.